Adoption of Digital Technology by Embroidery Entrepreneurs in Salatiga City (Case Study on Small Business Convection Persada, Tingkir) - Dhama Cristin Tegar Yuliana; Sri Sulandjari (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research explores the adoption of digital technology in embroidery in a case study at Konveksi Persada Tingkir. Technology adoption plays a vital role in determining productivity, innovation, and business journey. The development of embroidery technology will make the production process easier, starting from the use of computers in the sewing and embroidery process. The transition from manual embroidery techniques to computer-based embroidery is a strategic step to increase productivity, product quality, and business competitiveness in an increasingly competitive market. This research uses mixed methods, qualitative and quantitative with a case study method. At Persada Company, entrepreneurs who become owners and managers have considerations in adopting computer technology to increase customer satisfaction and expand target markets. When comparing the level of technological sophistication, computer embroidery relies more on technoware, while manual embroidery relies more on humanware. The adoption of computer embroidery technology was able to increase production speed up to five times compared to manual techniques, with an average production reaching 160 units per day. In addition, the accuracy of embroidery results increased by 1.16 times, with product defect rates reduced by 58%, providing a significant impact on operational efficiency. This technology also makes it easier for the production process, which previously relied heavily on the skills of human operators, to now become more automated and consistent in terms of final results. The results of this research show that the adoption of digital technology, especially computer embroidery, is an effective solution for improving the performance of small and medium enterprises in the textile and convection sectors.